(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the deposit policy of commercial banks and its impact on financial stability and liquidity management from a theoretical and practical point of view. Bank deposits are considered as the main factors affecting the long-term stability and liquidity risks of the banking system. Scientifically based proposals have also been developed to increase the efficiency of deposit attraction, minimize liquidity risks and maintain an interest policy flexible to macroeconomic changes.